Upaya Optimalisasi Lahan Bawah Tegakan pada Zona Tradisional melalui Sosialisasi Budidaya Nilam kepada Pengaram di Taman Hutan Raya K.G.P.A.A. Mangkunagoro I - Yus Andhini Bhekti Pertiwi; Malihatun Nufus; Rezky Lasekti Wicaksono; Rissa Rahmadwiati; Ana Agustina; Ike Nurjuita Nayasilana (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
The socialization of patchouli cultivation was conducted at Forest Park (Tahura) K.G.P.A.A. Mangkunagoro I, located at Mount Lawu, in Berjo Village, Ngargoyoso District Karanganyar Regency. Tahura K.G.P.A.A. Mangkunagoro I was divided into several zones. The most critical zone for the local community is the traditional zone. So far, the traditional zone was used by the community/forest farmers (pengaram) to plant grass (Pennisetum purpureum) under the main stand. The grass was planted mainly for animal feed or sale. During the dry season, the main problem was that the grass did not grow well. Thus, forest farmers do not have additional income from the traditional zone. For this reason, it was necessary to enrich understorey species that mainly have high economic and ecological values. One of the potential plants to be developed understands at traditional zone was patchouli (Pogostemon cablin Benth.). Patchouli is an essential oil-producing plant. It is easy to cultivate and has high economic value. The purpose of this community service was to provide knowledge to forest farmers about patchouli plants. The activities carried out in this program were providing counseling to forest farmers about the theory related to patchouli cultivation and its benefits, business opportunities, oil processing, and mentioned costs and income from patchouli cultivation. The result shows that the knowledge about patchouli cultivation was new for the forest farmers. Forest farmers and Tahura K.G.P.A.A. Mangkunagoro I staff showed interest in cultivating patchouli under forest stands in traditional zones.